Some features of reproduction and egg development of Stichaeus grigorjewi from Peter the Great Bay - Alexander I. Markevich; Valentina P. Gnyubkina (Известия ТИНРО, 2014)
Reproduction of long shanny Stichaeus grigorjewi is observed in natural conditions and its eggs embryogenesis is investigated in details in aquarium. The embryos and larvae of S. grigorjewi differ from other species by strong development of midbrain that assumes good eyesight forming. Duration of egg development and morphology of embryos and larvae coincide with earlier description made in Hokkaido, Japan, except of body ventral row of 10 melanophores described for S. grigorjewi larvae for the first time. The embryogenesis accelerates sharply under heightened water temperature.